RANKL and TNF-α-induced JNK/SAPK Osteoclastogenic Signaling Pathway was Inhibited by Caffeic Acid in RAW-D Cells - Ferry Sandra; Junita Briskila; Ketherin Ketherin (ISCC (Indonesian Journal of Cancer Chemoprevention))
Caffeic acid, a natural substance found majorly in fruits, grains, and herbs, is known to have therapeutic benefits. One of which is to inhibit bone resorption by targeting osteoclastogenesis through inhibition of the Cathepsin K, p38 Mitogenactivated Protein Kinase (MAPK), Nuclear Factor of Activated T-cells c1 (NFATc1) and Nuclear Factor kB (NFkB). Besides p38 MAPK, the c-Jun N-terminal kinase (JNK)/stressactivated protein kinases (SAPK), another member of MAPK family, has been reported to play important roles in osteoclastogenesis. Hence, current study was undertaken in order to investigate mechanism of Caffeic Acid towards JNK/SAPK pathway. Tartrate Resistant Acid Phosphatase (TRAP) staining was performed on caffeic acid-treated and RANKL-TNFα-induced RAW-D cells. Western blot analysis was performed to detect JNK/SAPK and phosphorylated-JNK/SAPK. Protein bands were quantified and statistically analyzed. Treatment of 10 μg/mL Caffeic Acid inhibited 20 ng/mL RANKL and 1 ng/mL TNFα-induced RAW-D differentiation into TRAP+ osteoclast-like polynuclear cells. Induction of 20 ng/mL of RANKL and 1 ng/mL of TNFa for 0.2 or 1 hour, significantly increase phosphorylation of JNK/SAPK as compared with control. Treatment of 10 μg/mL Caffeic Acid significantly inhibited the 20 ng/mL of RANKL and 1 ng/mL of TNFa-induced phosphorylation of JNK/SAPK. Taken together, Caffeic Acid could inhibit the RANKL and TNFa-induced osteoclastogenesis through JNK/SAPK.